Comparative energy and techno-economic analyses of two different configurations for hydrothermal carbonization of yard waste. (September 2019) - Akbari, Maryam; Oyedun, Adetoyese Olajire; Kumar, Amit
Abstract: Hydrothermal carbonization (HTC) includes conversion of wet biomass to hydrochar, a coal-like product, eliminating the need for biomass pre-drying. There has been limited focus on the techno-economic assessment of the HTC process in the literature. In this study, techno-economic models were developed to assess the economics of bio-coal production from yard waste for two different HTC plant configurations. In configuration A, heat is recovered by steam using several flash separators while in configuration B special heat exchangers are used. Process models were developed for the two configurations and then further used to estimate bio-coal production costs. The bio-coal cost and the net energy ratio (NER, or ratio of energy output to the energy input in the system) indicate that configuration A is preferable in terms of energy (NER of 5.2 versus 1.4 for configuration B) but less desired economically because it costs 3.3 $/GJ more than configuration B. Graphical abstract: Unlabelled Image Highlights: Bio-coal production costs of yard waste hydrothermal carbonization were calculated. Bio-coal cost is 2.1 $/GJ for a 960 t/d plant capacity. The net energy ratio for the process ranges from 1.4 to 5.2. Internal rate of return and capital cost have high influence on the bio-coal cost.